Analysis Effect of Light Intensity on Efficiency of the GH 100 WP-72 Solar Cell - Ferdi Kurniawan; Michael Dion Lisanto; Marselinus Angga Setyo Atmojo; Muhammad Hendra Budi Satria; Nellysa Arviana Tasya; Muhammad Iqbal Habibullah; Alvin Muhammad; Radissa Dzaky Issafira (BIOMEJ, 2024)
Energy is the main need today, with fossil energy sources increasingly depleting. Therefore, the development of renewable energy, such as solar energy, is very important. This article discusses the efficiency produced by solar cells in research conducted at the Energy Conversion Laboratory of the National Development University "Veteran" East Java. Solar cells are devices that convert solar energy into electrical energy through photovoltaic effects, without producing pollution or greenhouse gases, so they are an environmentally friendly energy source. Data was taken at 10.00-10.30, by measuring battery and solar panel voltage, battery charging current, and solar panel temperature. The experimental method was used by collecting data three times every 15 minutes for 30 minutes. The solar panel used is GH solar type GH 100 WP-72. Efficiency is calculated based on input and output power, with the highest efficiency achieved when the battery is full. The results show the lowest efficiency of 3.67% at 10.40 with a light intensity of 313.24 W/m² and the highest efficiency between 20.76% to 23.52% at 13.20-13.50 with a light intensity of 255.64 W/m² to 289. 61 W/m². Solar cell efficiency is greatly influenced by battery condition and light intensity.